2010
DOI: 10.1111/j.1439-0396.2009.00968.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute fasting and age on leptin and peroxisome proliferator-activated receptor gamma production relative to fat depot in immature and mature pigs

Abstract: Leptin and peroxisome proliferator-activated receptor gamma (PPARγ) are adipogenic proteins that are actively involved in metabolic homeostasis of fat. Recently, it was reported that fat tissue in humans and rodents differs in metabolic activity relative to anatomical location of the fat tissue (i.e. depots) and animal age. Hence, we hypothesized that leptin and PPARγ production in various fat depots in female pigs differs in response to acute fasting, and that these responses vary with physiological maturity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
3
5
0
Order By: Relevance
“…In our previous work [ 10 ], an 18 h fasting period affected the expression of the PPARG gene, which was activated after feeding, but had no effect on downstream genes. The actual results confirm that this unexpected, previous result was related, at least in part, to the duration of the fasting applied, as a 24 h period has a much more intense effect on gene expression, in agreement with other works [ 36 , 37 , 38 ]. Thus, a medium-long food deprivation period (24 h of fasting) seems to be necessary to stop lipogenesis in these fatty animals.…”
Section: Discussionsupporting
confidence: 92%
“…In our previous work [ 10 ], an 18 h fasting period affected the expression of the PPARG gene, which was activated after feeding, but had no effect on downstream genes. The actual results confirm that this unexpected, previous result was related, at least in part, to the duration of the fasting applied, as a 24 h period has a much more intense effect on gene expression, in agreement with other works [ 36 , 37 , 38 ]. Thus, a medium-long food deprivation period (24 h of fasting) seems to be necessary to stop lipogenesis in these fatty animals.…”
Section: Discussionsupporting
confidence: 92%
“…Probably, after short or medium fasting periods lipogenesis regulators are affected, while longer fasting periods may lead to a higher response in downstream genes. In fact, acute fasting (72 h) has been reported to produce greater effect on LEP than on PPARG genes expression (O'Gorman et al, 2010). On the other hand, results could be consistent with findings indicating that, in obese animals, de novo lipogenesis persist in liver and adipose tissue during fasting (Morgan et al, 2008).…”
Section: Discussionsupporting
confidence: 81%
“…Such results are in agreement with those of Robert et al (1998) who reported higher LEP mRNA abundance in the backfat tissue of fat (27.4 mm ± 5.5) versus lean (12.4 mm ± 1.6) barrows. Other authors reported higher leptin levels in pelvic than in subcutaneous and kidney adipose tissues of mature gilts (224 ± 7.4 d), whereas there was no difference in prepubertal gilts (132.2 ± 4.1 d) (O'Gorman et al, 2010). Current findings also suggest a different regulation of leptin transcription in various adipose tissue compartments since LEP mRNA abundance was lower in mammary extraparenchymal than in backfat adipose tissues.…”
Section: Discussionsupporting
confidence: 40%